SOIL PHYSICOCHEMICAL PROPERTIES AND BIO-AVAILABLE NUTRIENTS UNDER MANGLIETIA CONIFERA PLANTATION AT XUAN SON NATIONAL PARK, TAN SON, PHU THO - Thi Bich Phuong, Nguyen; Manh Hung, Bui; Thi Hang, Tran (Journal of Forestry Science and Technology, 2020)
Soil physicochemical properties and soil nutrient dynamics have reciprocal relationship with soil forming factors such as parent material, climate, topography and vegetation types. This study was conducted in three terrain positions under 20-year-old Manglietia conifera plantations including toe-slope and back slope and summit in Xuan Son National Park, Phu Tho province. Soil samples in each position were collected in three layers, including topsoil layer (0 - 10 cm), 10 - 20 cm layer and 20 - 50 cm layer. Research results showed soil proportion was 1.07 - 1.28g/cm3, soil density was 2.42 - 2.65g/cm3, soil porosity reached 49.34 - 59.88% and soil texture were sandy silt loam. Except for soil proportion and soil texture, soil density and porosity were different between terrain positions and soil depths. value was 4.97 - 6.23 and different between studied positions. Soil organic carbon (SOC) reached 1.92% - 3.56% classified from poor to medium of SOC and there was a great difference between the toe-slope and the summit. Bio-available nitrogen content was 1.02 - 2.59mg/100g, bio-available phosphorus content reached 0.1 to 0.26mg/100g and bio-available potassium content gained 2.56 - 6.17mg/100g. Except for bio-available phosphorus content, bio-available nitrogen and potassium contents were different between toe-slope and back slope. The bio-available content of N, P, K nutrients was proportional to soil organic matter, porosity, clay particle composition and pH. Meanwhile, soil density, sand and limon particles had an inverse relationship with bio-available N, P, K content. Soil physicochemical properties and soil nutrient dynamics have reciprocal relationship with soil forming factors such as parent material, climate, topography and vegetation types. This study was conducted in three terrain positions under 20-year-old Manglietia conifera plantations including toe-slope and back slope and summit in Xuan Son National Park, Phu Tho province. Soil samples in each position were collected in three layers, including topsoil layer (0 - 10 cm), 10 - 20 cm layer and 20 - 50 cm layer. Research results showed soil proportion was 1.07 - 1.28g/cm3, soil density was 2.42 - 2.65g/cm3, soil porosity reached 49.34 - 59.88% and soil texture were sandy silt loam. Except for soil proportion and soil texture, soil density and porosity were different between terrain positions and soil depths. value was 4.97 - 6.23 and different between studied positions. Soil organic carbon (SOC) reached 1.92% - 3.56% classified from poor to medium of SOC and there was a great difference between the toe-slope and the summit. Bio-available nitrogen content was 1.02 - 2.59mg/100g, bio-available phosphorus content reached 0.1 to 0.26mg/100g and bio-available potassium content gained 2.56 - 6.17mg/100g. Except for bio-available phosphorus content, bio-available nitrogen and potassium contents were different between toe-slope and back slope. The bio-available content of N, P, K nutrients was proportional to soil organic matter, porosity, clay particle composition and pH. Meanwhile, soil density, sand and limon particles had an inverse relationship with bio-available N, P, K content.